Explaining Demand for Higher Education - Oliveira, Manuela (2013)
Recognizing the crucial role of higher education for the development of nations and individuals, many countries have recently established ambitious targets for the percentage of graduates in their population by 2020. In peripheral European Union countries, however, such objectives may be difficult to attain. In fact, both the current stringent fiscal consolidation processes and the overall depressed economic environment may exert negative effects upon domestic demand for higher education. Such uncertain context increases the need for efficient policies and henceforth the value of obtaining reliable information on the variables that are more likely to influence demand. In this study, we employ the partial least squares methodology, which allows modeling with many variables, even with relatively few observations, to identify the most relevant determinants of demand for higher education. We focus in the case of Portugal, a country where applications for higher education are centralized and thus provides a long and reliable set of data on aggregate demand. The results of our empirical analysis suggest that the most relevant determinants of demand are institutional and/or policy dependent and, therefore, may be controlled by decision makers and managed to support national strategic objectives. These results, obtained for Portugal, are also useful particularly for other southern European Union countries, which share some of the Portuguese economic, social, demographic and cultural characteristics.